2007
DOI: 10.3748/wjg.v13.i48.6593
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment of hepatocellular carcinoma with partial splenic embolization and transcatheter hepatic arterial chemoembolization

Abstract: INTRODUCTIONTranscatheter hepatic arterial chemoembolization (TACE) has become the first choice of treatment for unresectable hepatocellular carcinoma (HCC) [1][2][3][4] . Since 70%-90% of HCC patients are associated with liver cirrhosis, portal hypertension and hypersplenism, treatment of HCC is usually affected by low peripheral blood cell counts (leukcytes, platelets and red blood cells) and high incidence of hemorrhagic complications due to treatment and/or portal hypertension [5][6][7][8] . Moreover, chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…In 1979, Spigos et al 40 first successfully used partial splenic arterial embolization (PSE) to treat hypersplenism. Subsequently, more clinicians [41][42][43] used PSE to treat portal hypertension, hypersplenism, and hemorrhage from esophageal and gastric fundal varices. PSE not only enhances PLT and WBC counts, 44,45 but also decreases splenic size, improves pancytopenia, 46 and induces immune function.…”
Section: Discussionmentioning
confidence: 99%
“…In 1979, Spigos et al 40 first successfully used partial splenic arterial embolization (PSE) to treat hypersplenism. Subsequently, more clinicians [41][42][43] used PSE to treat portal hypertension, hypersplenism, and hemorrhage from esophageal and gastric fundal varices. PSE not only enhances PLT and WBC counts, 44,45 but also decreases splenic size, improves pancytopenia, 46 and induces immune function.…”
Section: Discussionmentioning
confidence: 99%
“…PSE is a useful procedure to improve hypersplenism and portal hypertension and their complications [ 13 18 ]. However, there are only a few reports that are available about PSE in patients with HCC [ 19 – 21 ]. In those reports, PSE with TACE was mainly performed to decrease complications of portal hypertension such as variceal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the extent of splenic infarcted area after PSE was relatively high (77.0%), not only TACE but also PSE may have been involved in liver failure. Previous reports demonstrated that severe complications of PSE often develop when the extent of infarcted area is >70.0% [ 13 , 21 , 22 ]. Therefore, liver failure might develop after PSE even without simultaneous TACE in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Partial splenic arterial embolization (PSE) was first described by Spigos and colleagues 42 to treat hypersplenism. It has also been used to treat portal hypertension and esophagogastric variceal bleeding 43 , 44 . PSE not only can increase the counts of platelets and WBCs 45 – 48 , but can also reduce splenic volume and improve immune function 49 .…”
Section: Discussionmentioning
confidence: 99%